Assessing the Impact of the Leader Peptide in Protease Inhibition by the Microviridin Family of RiPPs - Stafford, Jillian L.; Montoya, Veronica K.; Bierman, Jeffrey J.; Walker, Mark C. (Biomedicines, 2024)
Background: Ribosomally synthesized and post-translationally modified peptides (RiPPs) are a growing class of natural products biosynthesized from a genetically encoded precursor peptide. RiPPs have attracted attention for the ability to generate and screen libraries of these compounds for useful biological activities. To facilitate this screening, it is useful to be able to do so with the leader peptide still present. We assessed the suitability of the microviridin family for these screening experiments by determining their activity with the leader peptide still present. Methods: Modified precursor peptides with the leader present were heterologously expressed in Escherichia coli. Their ability to inhibit elastase was tested with a fluorogenic substrate. HPLC was used to monitor degradation of the modified precursor peptides by elastase. SDS-PAGE was used to determine the ability of immobilized modified precursor peptide to pull down elastase. Results: We found that the fully modified precursor peptide of microviridin B can inhibit the serine protease elastase with a low nanomolar IC50, and that the fully modified precursor with an N-terminal His-tag can mediate interactions between elastase and Ni-NTA resin, all indicating leader peptide removal is not necessary for microviridins to bind their target proteases. Additionally, we found that a bicyclic variant was able to inhibit elastase with the leader peptide still present, although with a roughly 100-fold higher IC50 and being subject to hydrolysis by elastase. Conclusions: These results open a pathway to screening libraries of microviridin variants for improved protease inhibition or other characteristics that can serve as, or as inspirations for, new pharmaceuticals.